2020
DOI: 10.1177/0095798420924529
|View full text |Cite
|
Sign up to set email alerts
|

Impostor Phenomenon and Psychological Well-Being: The Moderating Roles of John Henryism and School Racial Composition Among Black College Students

Abstract: The impostor phenomenon (IP), or erroneous cognitions of intellectual incompetence, is a risk factor for poor psychological adjustment among Black emerging adults. Grounded in Lazarus and Folkman’s Stress and Coping Framework, the current study investigated John Henryism’s active coping and institutional racial composition as moderators of the association between IP and indicators of psychological well-being among 266 Black students (77% women; Mage = 19.87) attending predominatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 81 publications
(154 reference statements)
1
29
0
Order By: Relevance
“…There has been a growing body of research on the negative impact of the impostor phenomenon among Black college students (Bernard et al, 2020; Lige et al, 2017; Stone et al, 2018). Several studies have shed light on how the unique racialized experiences of Black individuals in primarily White institutions (PWIs) may contribute to the onset and/or maintenance of impostor feelings.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing body of research on the negative impact of the impostor phenomenon among Black college students (Bernard et al, 2020; Lige et al, 2017; Stone et al, 2018). Several studies have shed light on how the unique racialized experiences of Black individuals in primarily White institutions (PWIs) may contribute to the onset and/or maintenance of impostor feelings.…”
Section: Introductionmentioning
confidence: 99%
“…His quote illustrates that a lack of internalization of successes characterizes the IP as well as a pronounced self-doubt and a feeling of cheating (Clance and Imes, 1978 ). The fear of failing in future tasks and subsequently being exposed as an impostor is associated with restricted quality of life and career ambitions (e.g., Neureiter and Traut-Mattausch, 2016 ; Bernard et al, 2020 ). Thus, public and scientific interest in the IP has increased substantially over the last 6 years (e.g., Bravata et al, 2019 ; Mak et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence to suggest that for ethnic minority populations there is a racial component of impostor feelings 76,77 . For example, a recent qualitative study with Black graduate students found five themes related to impostor feelings: awareness of low racial representation, questioning intelligence, expectations, psychosocial costs, and explaining success externally 76 .…”
Section: Race / Ethnicity and Imposter Syndromementioning
confidence: 99%